Cross-National Variation in Glycemic Control and Diabetes-Related Distress Among East Asian Patients Using Insulin: Results from the MOSAIc Study. Issue 2 (June 2016) - Matsuba, Ikuro; Sawa, Tasuku; Kawata, Takehiro; Kanamori, Akira; Jiang, Dingfeng; Machimura, Hideo; Takeda, Hiroshi; Han, Jeong; Wang, Ke; Tanaka, Keiji; Shen, Li; Ajima, Miho; et al.
Abstract Introduction Guidelines recommend insulin progression for patients with type 2 diabetes (T2D) with inadequate glycemic control. The Multinational Observational Study Assessing Insulin use (MOSAIc [ClinicalTrials.gov identifier, NCT01400971]) study is a 2-year observational study, investigating factors that influence insulin progression in T2D patients. In this first of two reports, we describe baseline clinical and psychosocial characteristics of Chinese, Japanese, and South Korean patients who participated in MOSAIc. Insulin treatment, factors affecting progression, and outcomes will be reported separately. Methods Patients with T2D using insulin for ≥3 months were eligible. Baseline demographic, clinical, and psychosocial data were collected from patients. Quality of life instruments, including the Diabetes Distress Scale (DDS), were used to assess patient's concerns about disease management, support, and emotional burden. The association between the DDS and the selected covariates was also assessed. Results A total of 373 patients in China, 157 in Japan, and 141 in South Korea were enrolled from July 2011 to July 2013. Mean ± standard deviation duration (years) of T2D differed across countries (China 11.4 ± 7.5; Japan 13.8 ± 8.7; South Korea 15.7 ± 8.8;P  < 0.0001). Japanese patients used more noninsulin anti-hyperglycemic agents than did Chinese or South Korean patients (P  < 0.0001). Exclusive use of basal insulin was most common in Japan and South Korea compared with China, whereas approximately 66.8% of Chinese patients used mixed insulin. Covariates associated with the DDS were younger age [P  = 0.044 (Japan)], higher incidence of monthly hypoglycemia [P  = 0.036 [China];P  = 0.021 (South Korea)], and male gender [P  = 0.037 (South Korea)]. Conclusions There were significant differences amongst East Asian patients with T2D treated with insulin, including in quality of life scores. Results from the MOSAIc longitudinal analyses will further investigate trends of insulin intensification and barriers to insulin progression. Funding Eli Lilly and Company.